2021
DOI: 10.46827/ejes.v8i2.3555
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Teachers on Phases of the Moon and the Lunar Eclipse / Öğretmenleri̇n Ay'in Evreleri̇ Ve Ay Tutulmasina İli̇şki̇n Anlayişlari

Abstract: Even though the educational researchers have developed and implemented various educational strategies to teach the concepts of the phases of the Moon and the formation of the lunar eclipse more effectively, many studies conducted by them in recent years reveal that the teachers still do not understand the causes and scientific processes related to the phases of the Moon phases and lunar eclipse. In addition, this situation shows that there are deep problems in teaching the subjects of Moon phases and lunar ecl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The current study showed that 10 out of 14 interviewees did not construct a DMC based on scientific knowledge. This finding is in line with previous studies (e.g., Bayraktar, 2009;Kanli, 2014;Semercioğlu & Kalkan, 2021;Trumper, 2001;Trundle et al, 2002) that indicate individuals harbor misconceptions about phases of the Moon. Nonetheless, explanations not consistent with normative scientific explanations were not considered misconceptions in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study showed that 10 out of 14 interviewees did not construct a DMC based on scientific knowledge. This finding is in line with previous studies (e.g., Bayraktar, 2009;Kanli, 2014;Semercioğlu & Kalkan, 2021;Trumper, 2001;Trundle et al, 2002) that indicate individuals harbor misconceptions about phases of the Moon. Nonetheless, explanations not consistent with normative scientific explanations were not considered misconceptions in this study.…”
Section: Discussionsupporting
confidence: 93%
“…One of the popular nodes activated while explaining the Moon's phases is "shadow". More specifically, the phases of the Moon concept are often confused with the eclipse concept since they are related phenomena (Kanli, 2014;Semercioğlu & Kalkan, 2021). Furthermore, the location of an observer on Earth (Dunlop, 2000;Stahly, Krockover, & Shepardson, 1999), Earth's rotation (Baxter, 1989), and the distance between the Sun/Earth/Moon (Trundle et al, 2002) are other common conceptions regarding the cause of lunar phases.…”
Section: How Do Phases Of the Moon Occur?mentioning
confidence: 99%
“…The seasons and climate unit in the science curriculum is directly related to the geography course. However, since this subject was not included in previous science programs, it has been revealed in studies that teacher competencies in this subject are limited and misconceptions exist (Özcan et al, 2018;Semercioğlu et al, 2019). This situation is also valid for students, and it has been determined that students prefer to stay within stereotypes, have difficulty in presenting different perspectives, and have misconceptions especially about the position and movements of the Earth in space (Alkış, 2013;Bolat & Altınbaş, 2018;Boz, 2019;Özcan & Birgin, 2021;Özdemir et al, 2010;Sneider et al, 2011).…”
Section: Introductionmentioning
confidence: 99%